2015
DOI: 10.1016/j.concog.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Posture modulates implicit hand maps

Abstract: Several aspects of perception requires that immediate sensory signals be combined with information about the size and shape of the body, including binocular vision (Banks, 1988), and auditory localisation (Clifton et al., 1988). This need is especially acute in somatosensation, given that the primary receptor surface (the skin) is physically co-extensive with the body.Recent studies have investigated the nature of these body representations underlying somatosensory abilities such as position sense (e.g

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 48 publications
9
31
1
Order By: Relevance
“…Subsequent studies using this paradigm have replicated this basic pattern of results and extended them in several ways (e.g., Ferrè, Vagnoni, & Haggard, 2013;Longo, 2014Longo, , 2015bLongo & Haggard, 2012a, 2012bLongo, Long, & Haggard, 2012;Longo, Mancini, & Haggard, 2015b;Mattioni & Longo, 2014;Saulton, Dodds, Bülthoff, & de la Rosa, 2015). For example, Longo and Haggard (2012a) found that these distortions were smaller in magnitude when participants judged locations on the palmar surface of the hand.…”
Section: Distortions In Position Sensementioning
confidence: 55%
“…Subsequent studies using this paradigm have replicated this basic pattern of results and extended them in several ways (e.g., Ferrè, Vagnoni, & Haggard, 2013;Longo, 2014Longo, , 2015bLongo & Haggard, 2012a, 2012bLongo, Long, & Haggard, 2012;Longo, Mancini, & Haggard, 2015b;Mattioni & Longo, 2014;Saulton, Dodds, Bülthoff, & de la Rosa, 2015). For example, Longo and Haggard (2012a) found that these distortions were smaller in magnitude when participants judged locations on the palmar surface of the hand.…”
Section: Distortions In Position Sensementioning
confidence: 55%
“…Subsequent studies have replicated this general pattern, showing that perceived tactile distances appear to be systematically related to the sensitivity of different skin surfaces (e.g., Goudge, 1918; Marks et al, 1982; Cholewiak, 1999; Taylor-Clarke et al, 2004; Anema et al, 2008; Miller et al, 2016). Similarly, large anisotropies of perceived tactile distance have been reported on the limbs, with stimuli oriented across the width of limbs being perceived as substantially farther apart than stimuli oriented along the length of the limbs (Green, 1982; Longo and Haggard, 2011; Canzoneri et al, 2013; Longo and Sadibolova, 2013; Le Cornu Knight et al, 2014; Miller et al, 2014, 2016; Longo, 2015). For example, in the study of Longo and Haggard (2011), we presented participants sequentially with two pairs of touches on each trial, one pair oriented along the proximo-distal axis of their hand and the other oriented with the medio-lateral axis.…”
Section: Introductionmentioning
confidence: 91%
“…By comparing the relative locations of judgments of each landmark, an implicit perceptual map of the hand can be constructed and compared to the actual form of the hand. Studies using this paradigm have revealed a fat, squat hand representation, with overestimation of hand width and underestimation of finger length (e.g., Longo and Haggard, 2010, 2012a,b; Lopez et al, 2012; Ferrè et al, 2013; Longo, 2014, 2015; Mattioni and Longo, 2014; Coelho et al, 2016; Saulton et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…This overall pattern has been replicated numerous times in several labs (Cocchini et al in press;Coelho et al 2017;Coelho and Gonzalez in press;Ferrè et al 2012;Ganea and Longo 2017;Longo 2014Longo , 2015Longo , 2017bHaggard 2012a, 2012b;Longo et Response Type and Perceptual Hand Maps 4 al. 2012, 2015a, 2015bLongo and Morcom 2016;Lopez et al 2012;Mattioni and Longo 2014;Medina and Duckett 2017;Saulton et al 2015Saulton et al , 2016Saulton et al , 2017Stone et al 2018;Tamè et al 2017). Nevertheless, the interpretation of such effects remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…While my colleagues and I have interpreted these distortions as reflecting a central body model (e.g., Azañón et al 2016;Longo 2017a;Longo et al 2015a), some researchers have proposed that they may result from more general perceptual and motor processes (Medina and Duckett 2017;Saulton et al 2015Saulton et al , 2016Saulton et al , 2017.…”
Section: Introductionmentioning
confidence: 99%